The association between short interpregnancy interval and preterm births appropriate for gestational age among Malay women attending maternal child health clinics in Bachok, Kelantan, Malaysia - Mohd. Safiee bin Ismail
The objective of this study was to determine whether interpregnancy interval was associated with preterm births appropriate for gestational age among Malay women attending maternal child health clinics (MCH), in Bachok, Kelantan, Malaysia.This study used a case control study design based on 3294 delivery records from 6 health centers and 22 community clinics in 1997. Cases were preterm births and controls were term births with all appropriate for gestational age. Information were obtained from maternal delivery records and by maternal interview. Maternal record checklist and interview schedule were used for this purpose. Data were analyzed with logistics regression to control for potential confounders which included maternal age, maternal height, income, education, occupation, smoking, marital status, gestational weight gain, parity, first antenatal visit and frequency of visit. Interpregnancy interval was not associated with preterm births. However, the proportionn of preterm births was significantly lower in the interval of more than 36 months compared to the interval of less than or equal to 6 months.Based on the findings, it is possible that interpregnanc interval could not play as a significant risk factor for preterm births, at least not for this community. Therefore, in conducting health interventions to reduce the number of preterm infants, pregnancy spacing should not be the main focus of the activities.